DOI: 10.47328/ufvbbt.2021.088
|View full text |Cite
|
Sign up to set email alerts
|

Os papéis e desafios das organizações da agricultura familiar no abastecimento do Programa Nacional de Alimentação Escolar (PNAE) em municípios de Minas Gerais

Abstract: O objetivo desta pesquisa foi identificar e analisar os papéis e os desafios das cooperativas e associações no abastecimento do Programa Nacional de Alimentação Escolar (PNAE) em cinco municípios do estado de Minas Gerais: Belo Horizonte, Governador Valadares, Juiz de Fora, Montes Claros e Uberlândia, por meio do exercício da Lei n° 11.947/2009, que definiu que no mínimo 30% dos recursos do Fundo Nacional de Desenvolvimento da Educação (FNDE) destinados à alimentação escolar deve ser aplicados na aquisição de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The mean test was not statistically significant for any of these climatic variables in the last three intensity levels and indicates that access to Pronaf did not mitigate the negative effects. Climate change tends to disproportionately affect poor farmers in the Brazilian semi-arid region, Moreira et al (2014) found that some Pronaf B beneficiaries were forced to sell all their cattle to repay the loan by the end of the credit period. For the authors, these farmers struggled to generate income beyond subsistence levels due to unfavorable climate conditions and the fear of loan default.…”
Section: Impacts Of Pronaf Access: Typology Family Farming (Ff) -Pron...mentioning
confidence: 99%
“…The mean test was not statistically significant for any of these climatic variables in the last three intensity levels and indicates that access to Pronaf did not mitigate the negative effects. Climate change tends to disproportionately affect poor farmers in the Brazilian semi-arid region, Moreira et al (2014) found that some Pronaf B beneficiaries were forced to sell all their cattle to repay the loan by the end of the credit period. For the authors, these farmers struggled to generate income beyond subsistence levels due to unfavorable climate conditions and the fear of loan default.…”
Section: Impacts Of Pronaf Access: Typology Family Farming (Ff) -Pron...mentioning
confidence: 99%
“…Several authors claim that producer cooperatives are appropriate democratic organizations to address the dimensions of poverty reduction and social exclusion (Bijman & Wijers, 2019; Castilla‐Polo & Sánchez‐Hernández, 2020; Pouw & Gupta, 2017). Other authors also state that the cooperative sector, which involves cooperatives and organizations representing cooperatives in a given territory or country, is a strategic partner for the public sector in fulfilling its obligations to ensure healthy food and diet for the entire population (Freitas et al, 2021; León & Ramos, 2021). Cooperatives can thus be considered one of the organizations that most comprehensively represent institutionalized cooperation capable of transforming food systems.…”
Section: Analytical Perspective On Cooperatives: An Organizational Mo...mentioning
confidence: 99%